Biomarcadores Imunológicos do Envelhecimento Saudável em idosos de Belo Horizonte - Fernanda Calvo Fortes (2020)
The number of individuals over 80 years of age is growing worldwide. The process of aging is usually associated with an increase in physical incapacity and cognitive impairment. Immunosenescence describes a phenomenon of several immunological changes associated with aging that result in deficiencies in immune responses. It is also accompanied by a state of low-grade chronic sterile inflammation named inflammaging that is characterized by augmented levels of pro-inflammatory cytokines in aged people and is usually associated to increased risk of fragility and morbidity in the elderly with reduction of their quality of life. However, even with the presence of pro-inflammatory mediators, some aged individuals scape fragility and become healthy centenarians suggesting that several immunological functions can be remodeled and compensated by regulatory factors and mediators. Considering the importance of studies on healthy aging in Brazilian populations, we analyzed the plasma cytokine/chemokine profile as immune biomarkers of healthy aging in individuals over 80 years of age who live in Belo Horizonte as well as cognitive and functional parameters related to the degree of dependency in the elderly. Our data suggests that there are measurable changes in the levels of immune biomarkers related to the immune remodeling process such as G-CSF, MIP-1α, IFN-γ, IL-10, MCP-1, IL-15, among others. A positive and negative correlation between the cytokines and chemokines present (Spearman's correlation) was also evaluated, as well as a general assessment of the global cytokine profile (Radar Chart). In these three analyzes we suggest that longevity and aging are related to a balance between the systemic production of inflammatory and regulatory cytokines. These features were particularly relevant in the group of centenarians. The detection of early the risk of fragility through a combination of clinical features and immune biomarkers would help in the design of preventive measures to reduce fragility in its early stages promoting health (physical, cognitive and mental functions) and autonomy. It is still essential to establish a standardized criterion in the identification of fragility and further studies will be necessary to strengthen these results, as well as to fully establish immune biomarkers of healthy aging and fragility in the Brazilian population.